Hats off to the past - The Star, Tunku ' Abidin Muhriz (2012)
The greatest piece of parliamentary theatre takes place every Wednesday when the British Prime Minister takes questions from the Leader of Her Majesty's Most Loyal I Opposition and other MPs.